Behavior of Buccal Mucosal Squamous Cell Carcinoma: A Retrospective Study of 53 Carcinomas of this Anatomical Region. Issue 1 (March 2019) - Cariati, Paolo; Cabello Serrano, Almudena; Marin Fernandez, Ana; Julia Martinez, MiguelAngel; Fernandez Solis, Jose; Martinez Lara, Ildefonso
The main aim of the present report is to study the pattern of distribution of cervical metastasis in buccal mucosa cancer and to discuss the various therapeutic options available. Fifty-three patients with squamous cell carcinoma of the buccal mucosa treated with tumorectomy and selective neck dissection were included in the study. We also studied the relationship between specific pathological features and overall survival. Level Ib was the most affected level, followed by level IIa. T stage, N stage, N involvement tumor thickness, extracapsular spread (ECS), and vascular invasion were associated with poorer outcomes regarding overall survival ( p < 0.001). Carcinoma of the buccal mucosa should be treated aggressively from the early stages. A large tumorectomy of the primary tumor is required to reduce the number of local recurrences. Moreover, we recommend performing a supraomohyoid neck dissection even in cT1N0 if there is a suspicion that the tumor thickness may be greater than 0.4 cm. The high risk of local recurrence obliges protection of the neck from a future cervical recurrence even in T1 small tumors. This could reduce the risk of cervical involvement during the follow-up and improve overall survival rates.